PENGARUH JENIS AMELIORAN DAN DOSIS PUPUK SERBAGUNA (AGRODYKE) PADA PERTUMBUHAN RUMPUT GAJAH ODOT (Pennisetum Purpureum CV. Mott) DILAHAN GAMBUT - Yuliatul Muslimah; Yusrizal Yusrizal; Imaniah Refkikan (Universitas Teuku Umar, 2020)
Odot elephant grass is a tropical forage forage that is easily developed, has high production and can be used as animal feed.This study aims to determine the effect of ameliorant types and organic fertilizer (Agrodyke) doses on the growth of odot elephant grass (Pennisetum purpureum cv. Mott) on peatlands. This study used a 3x3 factorial randomized block design (RBD) with 3 replications consisting of: (1) ameliorant type factor (A) consisting of 3 levels, namely: A1 =dolomite lime, A2 = Shellfish shell, A3 = Eggshell. (2) Agrodyke fertilizer dose factor (D) Consists of 3 levels, namely: D0 = 0 gram / plant, D1 = 10 gram / plant, D2 = 20 gram / plant. Observation parameters are the number of leaves, number of shoots, leaf length, plant height. The results of this study indicate that the type of ameliorant did not significantly affect the number of leaves, number of shoots, leaf length, and plant height at 2 MST, 4 MST, and 6 MST. Versatile fertilizer (Agrodyke) dosage significantly affected the number of leaves and plant height at 6 MST. But no significant effect on the number of leaves, number of shoots and plant height in 2 MST and 4 MST. Keywords: Peat, Ameliorant Species, Odot Elephant Grass, Agrodyke.